Analysis Capabilities of Green Open Space and Quality Ambient Air Using Exhaust Gas Parameters on Motor Vehicles (CO2) (Case Study in Kendari City) - Satya Darmayani; Supiati Supiati; Lilin Rosyanti; Nanik Astuti Rahman; Wetri Febrina (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2024)
The rapid increase in population and land transportation in Kendari City has impacted the availability of green open spaces (GOS), which are crucial for maintaining air quality by absorbing carbon dioxide (CO2) emissions from motor vehicles. This study aims to assess the capacity of GOS in Kendari to absorb CO2 based on different vegetation types. The research employed a descriptive analysis method, with data collected through field observations and secondary sources, including information on GOS area, motor vehicle fuel consumption, and emission factors. The study found that Kendari City requires 17.73 hectares of GOS to absorb the CO2 emissions produced by motor vehicles, while the existing GOS covers 2,562.67 hectares. These indicate that the current GOS is sufficient to perform its environmental functions. Forests in the area absorb 10.292 tons of CO2, parks absorb 1.767 tons, green lanes absorb 27.682 tons, and other GOS areas, including the Kendari Botanical Gardens and sports fields, contribute more diminutive amounts. The results suggest that while Kendari's existing GOS can still manage CO2 emissions effectively, further expansion and optimization of green areas could enhance the City's environmental sustainability. This research provides valuable insights for urban planners and policymakers in Kendari, especially in planning for future GOS development to ensure continued air quality management.